Synthese und Struktur von N,N′-Diisopropylamidinat-substituierten Oligogallanen GanRnI2 (n ≤ 4) = Syntheses and structures of N,N′-diisopropylamidinate-substituted oligogallanes GanRnI2 (n ≤ 4) - Zessin, Thomas; Anton, Julian; Linti, Gerald W. (Zeitschrift für anorganische und allgemeine Chemie, 2013)
The reaction of galliumsubiodide with lithiumamidinates Li(NR)2CR′ results in formation of oligogallanes Gan(NR)2CR′nI2. The chains are built from up to four gallium atoms depending on the steric demand of the amidinates. All new compounds were characterized by NMR and crystal structure analysis and DFT calculations were used to evaluate structural variations.